Tinjauan Tentang Prosedur Pembayaran Hutang Oleh Account Payable Galaxy Hotel Banjarmasin Kepada Supplier - Muhammad Yasar; Huda Sya'rawi (P3M Politeknik Negeri Banjarmasin, 2022)
This research, aims to find out (1) the procedure for paying debts by accounts payable Galaxy Hotel Banjarmasin to suppliers, (2) obstacles in the process of paying debts by accounts payable Galaxy Hotel Banjarmasin. This research method is a form of descriptive research. The data sources used are primary and secondary data. The research variable is the independent variable. The data collection techniques of this study were observation, interviews and documentation. The data analysis technique used is qualitative. Based on the results of the study, the management of accounts payable used by Galaxy Hotel Banjarmasin's payable account has been running quite well and in accordance with applicable accounting procedures, although there are still some obstacles but overall it has been going quite well. This can be seen from the functions related to the payment of debts, the accounting records used, the documents used, and the network of procedures. There are several obstacles in the process of paying debts by Galaxy Hotel Banjarmasin's payable account to suppliers, namely: Transfer of debt payments that are not approved or approved for payment, differences in the quantity of goods on the supplier's invoice with the purchase order.